Why should Greylag Goose Anser anser parents rear offspring of others? - Nilsson, L; Kamp-Persson, H (Wildfowl, 2013)
The benefits and costs of rearing large broods were studied in a population of neck collared Greylag Geese in Scania, southernmost Sweden. Families were divided into four groups according to brood size: 1-4, 5-8, 9-12 and >12 young. Gosling survival showed a significant positive relationship with brood size on arrival at the rearing area. First-year and third-year local survival, as well as breeding recruitment, showed a significant positive relationships with brood size at fledging. For adults rearing large broods, no costs were detected during the year following that when they fledged >8 young; both survival rate and reproductive success exceeded the long-term averages.